PENGEMBANGAN ENSIKLOPEDIA IPA BERBASIS INTEGRASI-INTERKONEKSI ISLAM-SAINS SEBAGAI SUMBER BELAJAR MANDIRI PESERTA DIDIK MADRASAH TSANAWIYAH - Robi'ah Adawiyah; Ika Kartika (EDUSAINS, 2021)
DEVELOPMENT OF SCIENCE ENCYCLOPEDIA BASED ON INTEGRATION-INTERCONNECTION OF ISLAM-SCIENCE AS A SELF-LEARNING RESOURCES FOR MADRASAH TSANAWIYAH STUDENTSAbstractThe dichotomy of natural science and religion is a problem in Madrasas. The availability of learning resources in schools, especially madrasah tsanawiyah, which facilitates the integration and interconnection of Islam and science, is still very minimal, so teachers still have difficulty instilling Islamic values. This study aimed, 1) to produce a science encyclopedia product based on the integration-interconnection of Islam-science, 2) to know the quality of the science encyclopedia that has been developed, 3) to find out the responses of students and the implementation of the developed science encyclopedia. This research was development research. A 4-D model includes four stages: Define, Design, Develop, and Disseminate, which was used and limited to the Develop stage only. The research instruments were validation sheets, encyclopedia quality assessment sheets, and student response sheets. The results obtained that the quality of the development of science encyclopedias based on the integration-interconnection of Islamic science, the integration process of science material into verses of the Qur'an and hadith using an informative model is included in the Very Good classification based on the assessment of subject experts, linguists and graphic experts, integration-interconnection of Islamic science experts and science teachers. Students' responses to the limited test and broad test obtained was in the Agree classification.AbstrakDikotomi pembelajaran ilmu alam dan agama menjadi permasalahan di Madrasah. Ketersediaan sumber belajar di sekolah terutama madrasah tsanawiyah yang memfasilitasi integrasi-interkoneksi Islam dan sains masih sangat minim, sehingga guru masih kesulitan menanamkan nilai-nilai keislaman. Penelitian ini bertujuan, 1) menghasilkan produk ensiklopedia IPA berbasis integrasi-interkoneksi Islam-sains, 2) mengetahui kualitas ensiklopedia IPA yang telah dikembangkan, 3) mengetahui respon peserta didik dan keterlaksanaan ensiklopedia IPA yang telah dikembangkan. Penelitian ini adalah penelitian pengembangan. Menggunakan model 4-D meliputi 4 tahap: Define, Design, Develop, dan Disseminate yang dibatasi sampai tahap Develop. Instrumen penelitian berupa lembar validasi, lembar penilaian kualitas ensiklopedia, dan lembar respon peserta didik. Hasil diperoleh bahwa kualitas pengembangan ensiklopedia IPA berbasis integrasi-interkoneksi Islam sains, proses pengintegrasian dari materi IPA ke ayat Al-Qur’an dan hadis menggunakan model informatif termasuk kedalam klasifikasi Sangat Baik (SB) berdasarkan penilaian ahli materi, ahli bahasa dan grafika, ahli integrasi-interkoneksi Islam sains dan guru IPA. Respon peserta didik pada uji terbatas dan uji luas memperoleh klasifikasi Setuju (S).